"Making of Indian secularism: empire, law and christianity, 1830-1960" - "Chatterjee, Nandini" (New York, 2011)
This book tells two stories in one: the history of the formation of a secular state in India, and the story of Indian Christians, who played a tremendously important role in this process. Looking specifically at laws dealing with religious education, the management of religious institutions, family relations and property, it shows how Indian Christians provoked key historical debates about religion and law in British-ruled India, producing much of the state practices as well as political attitudes that define Indian secularism today. Using legal records, political pamphlets, private, missionary and government archives, the book demonstrates how Indian Christians shaped their own identity as a 'minority' community, while playing a disproportionately important role in shaping mainstream Indian culture. In doing so, it argues that the emergence of modernity has to be traced to its specific historical and local circumstances; in this case, India's encounter with imperial rule, and Indian Christians' particular experience of that encounter.
Keywords: Religious education-India